Morphology and Electrical Properties Study of Nanocrystalline Silicon Surface Prepared By Electrochemical Etching - Mohammad, Jamal Fadhil (Iraqi Journal of Science, 2022)
In this work, nanostructure porous silicon surface was prepared using electrochemical etching method under different current densities. I have studied the surface morphology and photoluminescence (PL) of three samples prepared at current densities 20, 30 and 40 mA/cm2 at fixed etching time 10 min. The atomic force microscopy (AFM) images of porous silicon showed that the nanocrystalline silicon pillars and voids over the entire surface has irregular and randomly distributed. Photoluminescence study showed that the emission peaks centered at approximately (600 – 612nm) corresponding energies (2.06 – 2.02eV).While current-voltage characteristics shows, as the current density increase the current flow in the forward bias is decreasing, while the rectification ratio and ideality factor varied from one sample to another. Finally, as etching current density increases the built in potential (Vbi) decreases (Vbi= 0.95, 0.75 and 0.55 volt corresponding 20, 30 and 40 mA/cm2) respectively.